Designing better donor strategies for inclusive business - Linda Kleemann (Kiel Institute for the World Economy (IfW), Poverty Reduction, Equity and Growth Network (PEGNet), 2016)
Inclusive business has been rising on the donor agenda for about ten years. Following Prahalad's (2004) book on 'Fortune at the Bottom of the Pyramid', there has been a shift within the donor community towards promoting business as a means of achieving development objectives. Donors see a chance of leveraging additional funding for development with the prospects of creating financially self-sustainable initiatives that scale up autonomously. A growing number of firms are interested in investing into low-income markets, and in collaborating with donors for their inclusive business activities. Several donors and development banks are active in this field and collaborate via platforms such as the Inclusive Business Practitioner Hub. This policy brief argues that a careful analysis of this web of business activities is needed, before and during any donor intervention in order to find a suitable intervention strategy, that highlights risks and - lacking evidence on impacts - asks where donors can be useful in supporting inclusive business. There are several working definitions of inclusive business that differentiate this concept from related ones.
Keywords: 330